EELS analysis of the nitrogen content of carbide particles in a commercial γ′-strengthened nickel-base superalloy. (October 2015) - Peterlechner, M.; Rösner, H.; Nembach, E.
Graphical abstract: Abstract : Carbide particles contribute to the high strength of nickel-base superalloys. It is a long standing question whether these carbide particles contain nitrogen. Here we examine the nitrogen content of the titanium–molybdenum-carbide in the commercial superalloy NIMONIC PE16 using a combination of electron energy loss spectroscopy (EELS) with energy dispersive X-ray (EDX) analysis. Careful examination of the molybdenum M3 - and M2 -edges, which overlap with the nitrogen K-edge, leads to an upper limit for the nitrogen content of the carbide: 1.8 at.%.